Assessment of levothyroxine therapy adequacy in low-risk differentiated thyroid carcinoma: a multicenter cohort study - Díez, Juan J.; Anda, Emma; Alcazar, Victoria; Galofré, Juan C.; Familiar, Cristina; Pamplona-Civera, María J.; González-Martínez, Silvia; Herrero-Ruiz, Ana; Alhambra, María R.; Planas, Alejandra; Sánchez-Ragnarsson, Cecilia; Martín, Tomás; et al. (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to evaluate the adequacy of levothyroxine therapy, assessed by serum thyrotropin (TSH) levels, in patients with low-risk differentiated thyroid carcinoma (DTC).MethodsWe conducted a multicenter, retrospective cohort study including patients with low-risk DTC. Dynamic risk stratification was performed 12 months after initial treatment and at the last follow-up visit according to the 2015 American Thyroid Association (ATA) guidelines. Patients were categorized based on treatment response as excellent, indeterminate, biochemical incomplete, and structural incomplete. Levothyroxine adequacy was determined according to ATA-recommended TSH target values.ResultsA total of 1016 patients (median age, 48 years; 80.7% women; 91.4% papillary thyroid carcinoma) were followed for a median of 6.6 years. Total thyroidectomy was performed in 935 (92.0%) (plus radioiodine in 667), while 81 (8.0%) underwent lobectomy. An excellent response was observed in 633 (62.3%) at 12 months and in 761 (77.8%) at the last follow-up. Treatment adequacy increased from 264 (26.0%) at 12 months to 387 (39.5%) at the final visit (P<0.001). Among patients with excellent response, treatment adequacy rose from 25.8% to 44.3% (P<0.001). At the last visit, inadequacy was primarily due to excessive levothyroxine in patients with excellent response (30.5%), and insufficient dosing in those with indeterminate or biochemical incomplete response (62.2% and 50.0%, respectively). Levothyroxine dose instability correlated significantly with treatment inadequacy (P<0.001).ConclusionThe low rate of treatment adequacy highlights the need of personalized levothyroxine dosing to optimize therapeutic outcomes and minimize the risks of under- or overdosing in patients with low-risk DTC.